(untitled) (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Chlamydiosis is of great global public health, veterinary and economic importance. This study aimed at determining the seroprevalence of chlamydiosis in Abu Dhabi camel (Camelus dromedarius) and its association with hematobiochemical responses towards the infection. Materials and methods: Blood samples (n=242) were collected from both housed and nomadic herds of camels. Anti-chlamydia antibodies were detected by an indirect enzyme-linked immunosorbent assay (ELISA). Camels had history of reproductive failure as abortion and repeat breeding. Besides, clinical reproductive examination was done with the camels. Results: Based on the results of ELISA, the overall seroprevalence of chlamydiosis was 19.59% (n=48/245). The hematological results revealed significant increase in the total hemoglobin concentration (15.65±0.28 gm/dL), hematocrit % (36.65±2.66%), mean corpuscular volume (37.35±0.83 U) and neutrophils % (72.05±0.89%) in the affected camels. The biochemical results revealed significant increase of the levels of alkaline phosphatase (61.50±3.56 IU/I), creatinine kinase (184.00±3.35 IU/I), and aspartate aminotransferase (64.50±3.42 IU/I). Nevertheless, significant reduction in glucose (42.25±1.97 mg/dL), choloride (107.03±0.53 mmol/L), and zinc (43.00±3.36 ug/dL) levels were observed in the affected camels. Conclusion: Chlamydiosis is prevailing among the Abu Dhabi camel. Chlamydiosis has great effect on the hematobiochemical parameters and reproductive performance of dromedary camels. Affected camels are suffered from reproductive failure manifested by abortion and/or repeat breeder. http://doi.org/10.5455/javar.2017.d208 XML PubReader